Optimal control of MIMO dead-time linear systems with dead-time compensation structure - Wilkley Bezerra Correia; Bismark Claure Torrico; René Descartes Olímpio Pereira (Dyna, 2017)
State space optimal controllers became popular over the last decades mainly because of its performance and robustness properties, as well as easy extension for multi-variable systems (MIMO). On the other hand, many industrial processes present dominant dead-time which may cause issues related to performance or even stability. Despite of its importance, few works from optimal control may be traced for this matter. In order to deal with dead-time effect one may use dead-time compensation (DTC) structures, mainly applied for single-variable systems (SISO). Within this context, this work proposes to modify a prediction structure recently proposed aiming to combine the best properties of both DTC and optimal control for MIMO linear systems. Simulation results along with the application to an experimental setup of a neonatal incubator prototype are presented to highlight the advantages and show the effectiveness of the proposed control strategy, as well as its practical aspect.